2020
DOI: 10.1021/acs.langmuir.0c00043
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Plasmon- and Green-Light-Induced Polymerization in Mesoporous Thin Silica Films

Abstract: The near-field of surface plasmon resonances at planar metal surfaces is confined to the nanoscale, but its resonance wavelength is located in the visible light range, making it interesting for confining polymer functionalization of surfaces but incompatible with the majority of polymerization reactions. Here, fluorescein as a polymerization initiator allowing dye-sensitized polymerization with green light (438−540 nm) is demonstrated to allow polymer functionalization of mesoporous films deposited onto planar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In further work, it was demonstrated that polymerization is indeed initiated via the photochemical mechanism and not by local temperature increase or hot electrons under the applied low irradiation energy. 50 Our research group 48,51,52 applied dye-sensitized visible-light induced photopolymerizations using a dye-tertiary amine photosensitizer, photoinitiator combination for mesoporous silica functionalization resulting in polymer-dominated gating of ionic mesopore accessibility. By using surface plasmons localized polymer functionalization in mesoporous layers was achieved (Fig.…”
Section: Free Radical Polymerizations Initiated By Visible Lightmentioning
confidence: 99%
“…In further work, it was demonstrated that polymerization is indeed initiated via the photochemical mechanism and not by local temperature increase or hot electrons under the applied low irradiation energy. 50 Our research group 48,51,52 applied dye-sensitized visible-light induced photopolymerizations using a dye-tertiary amine photosensitizer, photoinitiator combination for mesoporous silica functionalization resulting in polymer-dominated gating of ionic mesopore accessibility. By using surface plasmons localized polymer functionalization in mesoporous layers was achieved (Fig.…”
Section: Free Radical Polymerizations Initiated By Visible Lightmentioning
confidence: 99%
“…201,202 Dye-sensitized polymerizations only offer limited polymerization control but the polymer amount can be adjusted by the irradiation energy and reaction time and they can be combined with basically any plasmon source as an entire library of dyes, and thus initiation wavelengths, are commercially available. Thereby, controlled visible-light iniferterinduced polymerizations 203,204 are a very suitable polymerization reaction allowing polymerization control using grafting through or grafting from polymerizations induced by visible light including surface plasmons in mesoporous films. Nanolocal control could be demonstrated embedding plasmonic spherical Ag/Au alloy nanoparticles into mesoporous films.…”
Section: Transport Direction Via Asymmetric Nanopore Architecturementioning
confidence: 99%
“…This can be achieved using two photon processes, for instance . Alternatively, near-field modes, such as surface plasmons, offer a highly confined electromagnetic near field which is known to initiate polymerization, if compatible initiators are used. For example, successful polymer functionalization of mesoporous films deposited on planar gold or silver metal surfaces applying surface plasmons and dye-sensitized photopolymerization systems have been demonstrated in previous studies. , …”
Section: Introductionmentioning
confidence: 99%